Excess mortality according to group of causes in the first year of the COVID-19 pandemic in Brazil - Raphael Mendonça Guimarães; Mariana Passos Ribeiro Pinto Basílio de Oliveira; Viviane Gomes Parreira Dutra (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: To estimate excess mortality by cause of death in Brazil and states in 2020. Methods: We estimated the expected number of deaths considering a linear trend analysis with the number of deaths between 2015 and 2019 for each group of causes and each federative unit. We calculated standardized mortality ratios (SMR) and 95% confidence intervals for each SMR assuming a Poisson distribution. We performed the analyses in the R program, version 4.1.3. Results: We observed a 19% excess in deaths in 2020 (SMR=1.19; 95%CI=1.18-1.20). The Infectious and Parasitic Diseases group stood out among the defined causes (SMR=4.80; 95%CI 4.78-4.82). The ill-defined causes showed great magnitude in this period (SMR=6.08; 95%CI 6.06-6.10). Some groups had lower-than-expected deaths: respiratory diseases (10% lower than expected) and external causes (4% lower than expected). In addition to the global analysis of the country, we identified significant heterogeneity among the federative units. States with the highest SMR are concentrated in the northern region, and those with the lowest SMR are concentrated in the southern and southeastern regions. Conclusion: Excess mortality occurs during the COVID-19 pandemic. This excess results not only from COVID-19 itself, but also from the social response and the management of the health system in responding to a myriad of causes that already had a trend pattern before it.